Prolonged length of hospital stay and its associated factors among women after cesarean section in Guraghe zone public hospitals, Ethiopia - Mesfin Difer Tetema; Gudeta Beriso Jima; Legese Fekede Abza; Mebratu Demissie; Seid Jemal Mohammed; Ayele Sahile Abdo (BMC Pregnancy and Childbirth)
Abstract Introduction The length of hospital stay is an important indicator of quality peripartum and postoperative obstetric care. In light of this, the World Health Organization recommended that women stay in the hospital for 48–96 h after giving birth by cesarean. However, the length of stay varies between nations and institutions. The differences may have a variety of detrimental effects on the mother and/or on the infant. In Ethiopia, little is known about the duration of stay and the factors that affect it. This study aimed to determine the magnitude of prolonged length of hospital stay and associated factors among women who had cesarean sections in Gurage Zone public hospitals in Southern Ethiopia in 2023. Methods A facility-based cross-sectional study was conducted in public hospitals in Gurage Zone, Southern Ethiopia, from January 1, 2023 to May 30, 2023. A systematic sampling technique was used to select 423 study participants. The data was gathered through structured pretested interviews with mothers. After entering the data into Epi Data version 4.6, it was exported to the Statistical Package for Social Sciences version 25.0 for analysis. Bivariable and multivariable logistic regression analyses were used to assess factors related to prolonged hospital stay length. A p-value of less than 0.05 with a 95% confidence level was used to establish statistical significance in multivariable analysis. Result The average length of stay in Guraghe zone hospitals for mothers who gave birth via cesarean section was 73.4 h. Longer hospital stays were reported by 21.7% of respondents (95% CI, 17.3%, 26.2%). Longer hospital stay was associated with gestational age less than 37 weeks [AOR = 1.61 (1.04, 2.19)], birth weight less than 1500 g [AOR = 2.70 (1.80, 3.7)], birth weight between 1500 and 2500 g [AOR = 1.40 (1.03, 1.79)], and duration of membrane rupture greater than 24 h [AOR = 1.82 (1.06, 2.58)]. Conclusion Longer hospital stays after cesarean sections were common in the study area. It is critical to improve the recovery time of mothers who have had a preterm delivery, a low birth weight baby, or a prolonged rupture of membrane.